The Effect of Circuit Training on Concentration of Medical Students in Diponegoro University - Tiwik Budi Hastari; Yuriz Bakhtiar; Dimas Sindhu Wibisono; Zainal Muttaqin (Diponegoro International Medical Journal, 2020)
Background. Concentration has an important role that influences the success of the learning process. The higher the concentration of students in learning, the more effective learning and teaching processes are carried out. One of the benefits of exercise is the improvement of concentration. Lack of time and motivation to do physical exercise are some reasons why people do less exercise. Circuit Training is an exercise that does not require a lot of time and is becoming a trend now.Objective: To find out the effect of the Circuit Training on the concentration level of students at Medical Faculty of Diponegoro University.Method. This research was a quasi-experimental study with pre and post-test design, where research subjects were divided into two groups, there are the control group and the treatment group. The research subjects were 28 male students at Medical Faculty of Diponegoro University. The treatment group had given Circuit Training for 6 weeks. In one week there were 3 meetings where each training session was done in 3 circuits/cycle and each circuit consisted of 8 movements. The indicator assessed in this study was the level of concentration measured using the Digit Symbol Substitution Test (DSST) before and after Circuit Training for 6 weeks. The results were analyzed using SPSS.Results. The score of concentration in the treatment group increased with a pre-test score  64,93 ± 6,38 and post-test score 76,29 ± 5,74. Significant results (p = 0.001) were obtained in the pre and post-test treatment groups.Conclusion. Circuit training for 6 weeks can increase the concentration score of students at Medical Faculty of Diponegoro University.